2021
DOI: 10.1021/acsanm.1c02564
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into Direct Methane Oxidation to Methanol on Single-Atom Transition-Metal-Modified Graphyne

Abstract: Methane is the major component in natural gas and flares wastefully at remote sites since the collection and use are not economical. The direct conversion of methane into liquid fuels such as methanol has been identified as a fruitful solution to this issue. Herein, density functional theory calculations and microkinetic studies were employed on 3d late-transition-metal atom (Fe, Co, Ni, Cu)-loaded graphyne as catalysts for methane-tomethanol conversion. Single metal atoms showed decent stability at pores of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 70 publications
1
26
0
Order By: Relevance
“…Since reported in 2011, single-atom catalysts (SACs) have attracted wide attention in the field of catalysis and have been widely used in various catalytic reactions for high utilization of active metal atoms and high selectivity for target products, owing to unique geometric and electronic structure. Although it has been reported that SACs exhibited unique catalytic properties in the activation of CH 4 and conversion of CO 2 , there are rarely relevant reports on the use of SACs for co-conversion of CH 4 and CO 2 to acetic acid. Moreover, as an emerging high-efficiency nanocatalyst for CO 2 hydrogenation, the nanomaterial of indium oxide (In 2 O 3 ) aroused widespread concern and has been extensively investigated for synthesis of methanol from CO 2 experimentally and computationally, which also shows extremely high performance for activation of CO 2 when the surface oxygen vacancies exist. , In a previous research about acetic acid synthesis directly from CH 4 and CO 2 , metallic zinc had been proved to show a strong ability for the heterolytic dissociation of CH 4 and stabilization of methyl.…”
Section: Introductionmentioning
confidence: 99%
“…Since reported in 2011, single-atom catalysts (SACs) have attracted wide attention in the field of catalysis and have been widely used in various catalytic reactions for high utilization of active metal atoms and high selectivity for target products, owing to unique geometric and electronic structure. Although it has been reported that SACs exhibited unique catalytic properties in the activation of CH 4 and conversion of CO 2 , there are rarely relevant reports on the use of SACs for co-conversion of CH 4 and CO 2 to acetic acid. Moreover, as an emerging high-efficiency nanocatalyst for CO 2 hydrogenation, the nanomaterial of indium oxide (In 2 O 3 ) aroused widespread concern and has been extensively investigated for synthesis of methanol from CO 2 experimentally and computationally, which also shows extremely high performance for activation of CO 2 when the surface oxygen vacancies exist. , In a previous research about acetic acid synthesis directly from CH 4 and CO 2 , metallic zinc had been proved to show a strong ability for the heterolytic dissociation of CH 4 and stabilization of methyl.…”
Section: Introductionmentioning
confidence: 99%
“…As listed in Table , compared with one-dimensional material catalysts, for example, Pd-boron nitride nanotubes (0.89 eV), Pd-carbon nanotubes (1.11 eV), NCNT­(4,4)-O 2 (1.12 eV), and NCNT­(4,4)-O (1.08 eV), Ag–O–Ag/graphene and Cu–O–Ag/graphene catalysts both show lower activation energies of the C–H bond in CH 4 , which is mainly attributed to the strong composite interaction inducing high reactivity. In addition, it is the same in comparison with diverse two-dimensional composite catalysts, such as Co/G­(0.80 eV), Mn/G (0.99 eV), CoN 3 /G (0.83 eV), Fe@GY (0.98 eV), and OFe/N x G (1.34–1.91 eV), that is due to the introduction of noble metal Ag in Ag–O–Ag/graphene and Cu–O–Ag/graphene catalysts. As for the three-dimensional catalyst materials, zeolites have been widely studied.…”
Section: Resultsmentioning
confidence: 80%
“…For the Ag−O−Ag/ graphene catalyst, the C−H length in the reactant complex RC is 1.10 Å, which is the same as that of gas methane (1.10 Å) and close to that of the experimental value (1.09 Å), 57 58 and on the FeO/ graphene catalyst reported by Impeng et al 29 3, compared with one-dimensional material catalysts, for example, Pd-boron nitride nanotubes (0.89 eV), 60 Pd-carbon nanotubes (1.11 eV), 60 NCNT(4,4)-O 2 (1.12 eV), 61 and NCNT(4,4)-O (1.08 eV), 61 Ag−O−Ag/ graphene and Cu−O−Ag/graphene catalysts both show lower activation energies of the C−H bond in CH 4 , which is mainly attributed to the strong composite interaction inducing high reactivity. In addition, it is the same in comparison with diverse two-dimensional composite catalysts, such as Co/G(0.80 eV), 62 Mn/G (0.99 eV), 62 CoN 3 /G (0.83 eV), 63 Fe@GY (0.98 eV), 64 and OFe/N x G (1.34−1.91 eV), 47 31 and Pt 2 /GO sheet (0.33 eV), 66 which also means that the presence of these noble metal catalysts can easily realize CH 4 activation. 67 As for the CH 3 OH* formation, the CH 3 * group breaks the bond with the metal atom and connects with μ-OH to form Moreover, with the help of differential charge density, the electronic properties related to catalytic activity are investigated.…”
Section: Models Of Ag−o−ag/graphene and Cu−o−ag/graphenementioning
confidence: 84%
“…[46,363] Furthermore, single iron atoms have been shown to be more effective due to Fe-O active centers, which may easily break C-H bonds and catalyze subsequent CH 4 oxidation to formic acid through accessible radical pathways under mild conditions. [364,365] For example, Cui et al demonstrated that at normal temperature (25 °C), H 2 O 2 could directly oxidize CH 4 to C1 oxygenates (CH 3 OH, CH 3 OOH, HOCH 2 OOH, and HCOOH) over graphene-confined single-atom Fe (FeN 4 ) catalysts. In addition, according to DFT calculations and electron paramagnetic resonance studies, the unique O-FeN 4 -O structure was the active site for CH 4 oxidation along a radical pathway to yield CH 3 OH and CH 3 OOH with a low barrier of 0.79 eV.…”
Section: Thermocatalysis For Partial Oxidation Of Methane In Liquid-p...mentioning
confidence: 99%